Analysis of Telecommunication Market Competition in Indonesia: A Case Study of the XL-SMART Merger - Muhammad Fajar Ariwibowo; Azalia Mawarindani Indra; Umari Abdurrahim Abi Anwar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
PT XL Smart is a merger company carried out by XL Axiata, Smartfren Telecom, and Smart Telcom with a merger value of more than Rp 104 trillion. PT XL Smart has advantages in brands and is able to serve markets from various circles. This research activity will focus on business competition in the telecommunications sector in Indonesia, which continues to grow, and appropriate merger regulations to prevent unfair competition practices from the merger action or even the potential for an oligopoly market. The research method used qualitative descriptive, the analysis in this study is also using competition law in Indonesia which also regulates the merger of companies. The results are telecommunications market competition is increasingly competitive, XL Smart has the opportunity to become a market leader, and the main challenge after the merger is that different corporate cultural barriers can be overcome with ICare values. In terms of the company's strengths after the merger, XL Smart can have complementary competitive advantages and has the opportunity to overcome the weaknesses it has after the merger.